An investigation into the influence of zinc precursor on the microstructural, photoluminescence, and gas-sensing properties of ZnO nanoparticles - Catto, Ariadne C. [UNESP]; Silva, Luis F. da [UNESP]; Bernardi, Maria I. B.; Li, Maximo S.; Longo, Elson [UNESP]; Lisboa-Filho, Paulo N. [UNESP]; Nascimento, Otaciro R.; Mastelaro, Valmor R. (Springer, 2014)
This paper describes the effect of different zinc precursors, acetate, oxide, and nitrate, on the structure, microstructure, photoluminescence, and ozone gas-sensing properties of zinc oxide (ZnO) nanoparticles. Transmission and scanning electron microscopy, and BET surface area show a dependence of the particle size and surface area with the precursor type. The ZnO sample synthesized from zinc nitrate shows the best photoluminescence (PL) emission. Although electron paramagnetic resonance shows in all samples the presence of a g-signal attributed to oxygen vacancies, it is not possible to correlate the presence of these defects with PL emission behavior. Furthermore, ZnO sample synthesized from zinc nitrate also shows the best ozone gas-sensing response, however, our results do not allow correlating the best PL emission in the visible region with the best sensor response to ozone gas.
Keywords: Zinc oxide; Nanocrystalline materials; Microstructure; Photoluminescence; Gas sensor